Analisis Perbandingan Kinerja Keuangan Bank dalam Masa Pandemi Covid 19 - Deka Gustina Pandiangan; Ihsan Effendi; Adelina Lubis (Mahesa Research Center, 2022)
During the pandemic period, the banking industry is expected to have an impact on the economic waves that occurred in Indonesia. The Indonesian financial system can be distinguished from conventional and Islamic financial systems. This study aims to determine the differences in the ratios of Islamic Commercial Banks (BUS) and Conventional Commercial Banks, including Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Return ON Assets (ROA), Operating Expenses and Operating Income (BOPO) and Loans. to Deposit Ratio (LDR) for the last 4 years. Comparison of the performance of financial ratios at Islamic Commercial Banks and Conventional Commercial Banks as measured by the ratio of Capital Adequay Ratio (CAR), Non Performing Loan (NPL), Return On Assets (ROA), Return On Assets (ROA), Operating Expenses, Operating Income ( BOPO) are the same in the sense that there is no difference between the ratios. For the Loan to Deposit Ratio (LDR) there are differences in the financial performance of Islamic Commercial Banks and Conventional Commercial Banks.